Menakar Arah Demokrasi Konstalasi Partai Politik Dalam Proses Pemilihan Umum Pasca Reformasi - Fakhrurrozi Arrusadi (Lex Renaissance, 2020)
The purpose of this study is to identify and further examine whether the role of political parties has reached the direction of democratic political consolidation after the 1998-2019 Reformation. The research method used is normative method by utilizing secondary data sources obtained through literature, books, legal materials, etc. The results of the study conclude that the role of political parties is still lacking in carrying out their functions as participatory political communities in democracy. The orientation of political parties is only used as a means to obtain the legality of power in the political struggle of general election democracy, including the role of political parties that tend to be oligarchic, political parties sometimes act loudly for and on behalf of the people's interests, but in fact they fight for the interests of their administrators. themselves, namely the elite and party rulers